Low-defect wave-absorbing foam material and preparation method thereof

By synergistically designing modified polyurethane resin and composite absorber, and combining a staged temperature-controlled stirring process, the problems of cell structure defects and insufficient high-frequency absorption were solved, thereby improving cell uniformity and high-frequency absorption performance to meet the absorption requirements of the 5G millimeter-wave band.

CN120904666AInactive Publication Date: 2025-11-07LUOYANG SIWEINUO NEW MATERIALS TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511415141.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-30
Publication Date
2025-11-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing absorbing foam materials suffer from problems such as difficulty in controlling defects in the cell structure and insufficient absorption capacity in the high-frequency band, resulting in uneven pore size and poor absorption performance, which cannot meet the requirements of the core frequency band of 5G millimeter wave.

Method used

A method using low-dielectric modified polyurethane resin, composite microwave absorber, and staged temperature-controlled stirring is employed. This method involves adjusting the bubble growth rate with an organosilicon foaming agent, promoting the dispersion of the microwave absorber with fatty alcohol phosphate ester, and enhancing the bubble wall strength with hollow glass microspheres. Combined with the three-level structure of La-Ce co-doped NiZn ferrite core and Ti3C2TXMXene/ZrO2 composite layer, synergistic loss is achieved, and the dielectric gradient is optimized to ensure that electromagnetic waves fully penetrate the material and are lost.

Benefits of technology

It improves the uniformity of the bubble structure and the absorption performance in the high-frequency band, meets the performance consistency requirements of precision electronic equipment, significantly enhances the absorption capability of the 45-70GHz band, and covers the needs of the core frequency band of 5G millimeter wave.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and particularly discloses a low-defect wave-absorbing foam material and a preparation method thereof. The invention relates to a low-defect wave-absorbing foam material, which comprises the following raw materials: 45-65 parts of low-dielectric modified polyurethane resin; 10-18 parts of a composite wave absorbing agent; 2-6 parts of hollow glass beads; 3-6 parts of an organic silicon foam stabilizer; 1-3 parts of nano calcium carbonate; 1-3 parts of fatty alcohol phosphate; 0.5 to 1.5 parts of an antioxidant; 1-4 parts of a cross-linking agent; 4-8 parts of a foaming agent; the low dielectric modified polyurethane resin is organic silicon modified polyurethane; according to the composite wave absorbing agent, La-Ce co-doped NiZn ferrite is used as a core, and a Ti < 3 > C < 2 > T < X > M < X > ene / ZrO2 composite layer is used as a shell. According to the wave-absorbing foam material, the uniformity of the pore diameter of the foam pores is effectively enhanced, and the wave-absorbing performance of the wave-absorbing material at a high frequency band is effectively enhanced through the low-dielectric modified polyurethane resin and the composite wave-absorbing agent.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of high polymer materials, and more particularly to a low-defect wave-absorbing foam material and a preparation method thereof. BACKGROUND

[0002] With the rapid development of 5G communication, terahertz imaging, advanced radar detection and other technologies, electromagnetic interference and electromagnetic compatibility problems are increasingly prominent. As the core carrier for solving this problem, the performance of wave-absorbing materials directly determines the stability and safety of electronic devices. Wave-absorbing foam materials, which have the advantages of light weight, low dielectric constant and strong designability, have become key materials in the fields of electromagnetic shielding, high-frequency communication and precision medical treatment (such as nuclear magnetic resonance equipment). The wave-absorbing performance of such materials essentially depends on the internal pore structure. Uniformly distributed pores can cause multiple reflections and scattering of electromagnetic waves, prolong the propagation path and achieve energy loss through wave-absorbing agents. Therefore, the integrity and uniformity of the pore structure are the key factors determining the lower limit of its performance. If the pore size is uneven, there are cavities or broken pores, it will cause local penetration or reflection of electromagnetic waves, directly reducing the absorption efficiency.

[0003] At present, in the related technology, a patent document with publication number CN114883813B discloses a kind of foam carbon wave-absorbing material and its preparation method and application. The raw material content of the wave-absorbing material includes: foaming component A, foaming component B, polyurethane foaming ingredients A, ammonium polyphosphate, expanded graphite powder, molybdenum trioxide, organic silicon foam stabilizer, foaming component B and polyurethane foaming ingredients B. The foaming component A includes polyurethane foaming ingredients A, ammonium polyphosphate, expanded graphite powder and molybdenum trioxide. The foaming material has the advantages of high yield, low cost and good absorption performance, providing a feasible solution for the industrialization of wave-absorbing foam materials.

[0004] However, the wave-absorbing material in the above-mentioned technology still has obvious technical shortcomings in actual application: first, the pore structure defects are difficult to control. Even with the addition of organic silicon foam stabilizer, the multi-ingredient mixing foaming process is still prone to uneven component dispersion and foaming rate fluctuations, resulting in pore agglomeration, cavities or broken pores, and uneven pore size, which cannot meet the performance consistency requirements of precision electronic devices. Second, the high-frequency absorption capacity is insufficient. The wave-absorbing agent, such as expanded graphite powder, can only achieve magnetic loss in the 1-18GHz low-frequency band, while in the 45-70GHz 5G millimeter wave core frequency band, the magnetic permeability decreases sharply and the dielectric matching is poor, resulting in poor absorption performance in this frequency band and inability to cover high-frequency scene requirements. Therefore, it is an urgent need in the current high polymer wave-absorbing material field to develop a low-defect wave-absorbing foam material with uniform pore structure and effective absorption of 45-70GHz high-frequency electromagnetic waves. SUMMARY

[0005] In order to improve the pore uniformity and the wave absorption performance of the wave absorption material at high frequency, the application provides a low-defect wave absorption foam material and a preparation method thereof.

[0006] The low-defect wave absorption foam material provided by the application adopts the following technical scheme: A low-defect wave absorption foam material comprises the following raw materials by weight: Low-dielectric modified polyurethane resin 45-65 parts; Composite wave absorption agent 10-18 parts; Hollow glass microbeads 2-6 parts; Organic silicon foam stabilizer 3-6 parts; Nano calcium carbonate 1-3 parts; Fatty alcohol phosphate 1-3 parts; Antioxidant 0.5-1.5 parts; Crosslinking agent 1-4 parts; Foaming agent 4-8 parts; The low-dielectric modified polyurethane resin is an organic silicon modified polyurethane; The composite wave absorption agent takes La-Ce co-doped NiZn ferrite as the core, Ti3C2T X MXene / ZrO2 composite layer as the shell.

[0007] By adopting the above technical scheme, the low-dielectric modified polyurethane resin is an organic silicon modified system, the dielectric constant is close to that of air, and the viscosity and fluidity of the base material are matched, which provides a basis for uniform mixing of various components, avoids the blockage of cell growth caused by poor fluidity of the base material, the dielectric constant is close to that of air, which can reduce the surface reflection of high-frequency electromagnetic waves, ensure that electromagnetic waves fully enter the material interior and be lost, and thus improve the wave absorption performance of the wave absorption material. Hollow glass microbeads can enhance the mechanical strength of the cell wall and avoid cell wall rupture during foaming; nano calcium carbonate can fill the small gaps between the base material and the wave absorption agent, reduce the generation of cavities, and thus improve the pore uniformity of the wave absorption material. The organic silicon foam stabilizer can reduce the gas-liquid interfacial tension, make the bubble growth rate uniform, and avoid the formation of large pores by local excessive foaming; the fatty alcohol phosphate can promote the uniform dispersion of the composite wave absorption agent and avoid the formation of solid areas without pores caused by the agglomeration of the wave absorption agent, thereby further enhancing the uniformity of the pore diameter of the wave absorption material.

[0008] The composite wave absorption agent takes La-Ce co-doped NiZn ferrite as the core, Ti3C2T X MXene is the intermediate layer shell, and ZrO2 is the outer layer shell, and the three-level structure forms synergistic loss: La 3+ / Ce 4+The doping regulates the magnetocrystalline anisotropy constant, suppresses the magnetic moment relaxation hysteresis at high frequency, ensures that the magnetic permeability is greater than or equal to 0.3 in the frequency band of 45-70 GHz, and thus provides stable magnetic loss; the MXene layer has high electrical conductivity, and consumes high-frequency electromagnetic wave energy through electrical conduction loss; the outer ZrO2 layer has a dielectric constant ε' of about 20-25, and a dielectric gradient of "air→ZrO2→MXene→ferrite" is constructed to reduce the surface reflection of high-frequency electromagnetic waves, thereby effectively improving the wave absorption performance of the wave absorption material at high frequencies.

[0009] Optionally, the low-dielectric modified polyurethane resin is prepared by the following method: The polyester polyol, the chain extender and the auxiliary agent are mixed and stirred at 70-80 DEG C for 1-2 h, then the polydimethylsiloxane is added, and stirring is performed at 100-110 DEG C at a speed of 1000-1500 rpm for 30-60 min, and then the stirring is stopped to obtain a gel-like substance, which is poured into a mold for curing, and then broken to obtain the low-dielectric modified polyurethane resin.

[0010] By using the above technical solution, the dielectric constant of the organic silicon modified polyurethane prepared by the above method is stable and has small deviation, the surface reflection of high-frequency electromagnetic waves can be reduced, the electromagnetic waves can be ensured to fully enter the material interior to be lost, and thus the wave absorption performance of the wave absorption material is improved. High-speed stirring can break the local gel groups that may be formed during polymerization, ensure uniform dispersion of PDMS, avoid fluctuations in the dielectric constant of the substrate caused by PDMS agglomeration, and thus enhance the performance stability of the low-dielectric modified polyurethane resin.

[0011] Optionally, the low-dielectric modified polyurethane resin has the following raw material ratio by weight: 40-70 parts of polyester polyol, 3-10 parts of chain extender, 30-50 parts of polydimethylsiloxane and 0.5-1.5 parts of auxiliary agent.

[0012] By using the above technical solution, the above ratio can make the flowability of the low-dielectric modified polyurethane resin adapt to the subsequent foaming process, avoid uneven growth of the cells due to poor flowability, or escape of bubbles to form cavities due to too strong flowability during foaming, and thus facilitate improvement of the uniformity of the cell diameter of the wave absorption material.

[0013] Optionally, the chain extender is at least one of 1,4-butanediol and ethylene glycol; and the auxiliary agent is antioxidant 168.

[0014] Optionally, the composite wave absorption agent is prepared by the following method: A. Mix raw materials Fe2O3, NiO, ZnO, La2O3 and CeO2, add deionized water, ball mill for 6-8 h to obtain a slurry, add PVA glue, continue to ball mill, then spray granulation, and then sinter at 1150-1250°C for 1-2 h, and obtain La-Ce co-doped NiZn ferrite after cooling; B. Disperse the La-Ce co-doped NiZn ferrite in Ti3C2T X MXene dispersion liquid, ultrasonic treatment for 40-80 min, stirring reaction at 65-85°C for 3-5 h, to obtain ferrite@MXene core-shell particles; C. Disperse the ferrite@MXene core-shell particles in ZrO2 sol, adjust the pH to 8.0-9.0, and age at 50-60°C for 2-3 h, dry at 120-150°C for 4-6 h after centrifugation to obtain a composite wave absorber.

[0015] By adopting the above technical scheme, the preparation method ensures high purity of the ferrite core, uniform doping, and complete MXene / ZrO2 composite layer coating, avoiding the problem of incomplete structure in the traditional one-step method. The prepared wave absorber has a complete core-shell structure, uniform particle size, and uniform distribution of doping elements, which can significantly improve the synergy of magnetic loss and dielectric loss in the high frequency band, providing protection for the high frequency wave absorption performance of the material. From the mechanism, each step respectively realizes the full mixing and stable doping of raw materials, the uniform coating of MXene to form a dielectric loss layer, and the complete coating of ZrO2 to construct a dielectric gradient, thereby optimizing the high frequency impedance matching.

[0016] Optionally, in step A, the mass ratio of Fe2O3, NiO, ZnO, La2O3 and CeO2 is (65-70):(10-13):(18-22):(1.2-2.0):(0.8-1.5).

[0017] Optionally, in step B, the mass ratio of the La-Ce co-doped NiZn ferrite to Ti3C2T X MXene dispersion liquid is 1:(2-4); the mass ratio of the Ti3C2T X MXene dispersion liquid is 1:(2-4); the mass ratio of the Ti3C2T X The solid content of the MXene dispersion liquid is 10%-15%.

[0018] By adopting the above technical scheme, the mass ratio of the La-Ce co-doped NiZn ferrite to Ti3C2T X MXene dispersion liquid and the solid content of the dispersion liquid, avoiding the over-thickness or over-thin coating of MXene, and ensuring the balance of dielectric loss and impedance matching.

[0019] Optionally, in step C, the mass ratio of the ferrite@MXene core-shell particles to ZrO2 sol is (4-3):1.

[0020] By adopting the technical scheme, the above-mentioned proportioning ensures that the thickness of the ZrO2 outer layer is moderate, the dielectric gradient optimization effect is optimal, and the high-frequency impedance matching performance is further improved. The uniform ZrO2 outer layer avoids the deviation of the wave absorption performance caused by the thickness fluctuation.

[0021] Optionally, the organosilicon foam stabilizer is any one of polyether modified polysiloxane and fluorosilicon modified polysiloxane.

[0022] In a second aspect, the application provides a preparation method of a low-defect wave-absorbing foam material, which adopts the following technical scheme: A preparation method of a low-defect wave-absorbing foam material, comprising the following steps: S1, adding a low-dielectric modified polyurethane resin into a mixer, heating to 50-60℃, adding a composite wave-absorbing agent and a fatty alcohol phosphate, stirring at a speed of 800-1000 rpm for 15-20 min to obtain a pre-dispersion liquid; S2, sequentially adding hollow glass microspheres, nano calcium carbonate, an organosilicon foam stabilizer, an antioxidant and a crosslinking agent into the pre-dispersion liquid of S1, heating to 65-75℃, stirring at a speed of 600-800 rpm for 25-35 min, finally adding a foaming agent, stirring for 5-8 min to obtain a foaming slurry; S3, injecting the foaming slurry into a mold preheated to 40-45℃, pre-foaming at 45-50℃ for 15-20 min, then heating to 65-70℃ for main foaming for 25-30 min; after foaming, heating to 85-90℃ for curing for 30-40 min, cooling to room temperature, then demolding to obtain a low-defect wave-absorbing foam material.

[0023] By adopting the technical scheme, the low-temperature stirring in S1 stage can avoid the early softening and agglomeration of the base material, and the high-speed stirring and the fatty alcohol phosphate can synergistically promote the dispersion of the wave-absorbing agent; the medium temperature in S2 stage can improve the fluidity of the base material, ensure the uniform distribution of the fillers such as hollow glass microspheres and nano calcium carbonate, and the low-speed addition of the foaming agent can avoid the early decomposition of the foaming agent; the pre-foaming in S3 stage can control the initial growth of bubbles and avoid large pores, the main foaming at 65-70℃ can promote the uniform expansion of bubbles, and the curing at 85-90℃ can ensure the complete crosslinking reaction, thereby improving the strength of the cell wall and avoiding deformation after demolding.

[0024] In summary, the application has the following beneficial effects: 1、The application can adjust the bubble growth rate by using silicone uniform bubble agent, avoid local excessive foaming to form large pores; fatty alcohol phosphate can promote the uniform dispersion of the composite wave-absorbing agent, prevent the formation of solid area without pores due to the agglomeration of the wave-absorbing agent; hollow glass microspheres can enhance the strength of the pore wall, reduce the pore rupture, and nano calcium carbonate can fill the small gaps to reduce the probability of cavity formation. Stage temperature control and stirring ensure that the components are fully mixed, and avoid uneven dispersion of raw materials; segmented foaming controls the initial growth of bubbles, and then promotes the uniform expansion of bubbles, further reducing the size difference of the pores. Finally, the pore structure defects are effectively solved, the pore size uniformity is improved, the material performance stability is significantly enhanced, and the performance consistency requirement of precision electronic equipment is met.

[0025] 2、The application solves the problems of traditional wave-absorbing materials, such as sudden drop of magnetic permeability in 45-70GHz high frequency band, poor dielectric matching, and poor absorption performance. The application realizes breakthrough through the structural innovation of composite wave-absorbing agent and the design of low dielectric system. The three-level core-shell structure of the composite wave-absorbing agent forms a synergistic loss effect: La-Ce co-doped NiZn ferrite core can inhibit the magnetic moment relaxation hysteresis at high frequency, and provide stable magnetic loss; the MXene intermediate layer realizes dielectric loss by high electrical conductivity, and consumes high-frequency electromagnetic wave energy; the ZrO2 outer layer constructs a dielectric gradient, reduces the surface reflection of high-frequency electromagnetic waves. At the same time, the low dielectric modified polyurethane resin and the hollow glass microspheres synergistically optimize the impedance matching, ensuring that the electromagnetic wave fully enters the material interior to be lost. The overall design greatly improves the absorption capacity of the material in the 45-70GHz frequency band, effectively covering the 5G millimeter wave core frequency band requirement. DETAILED DESCRIPTION

[0026] The application will be further described in detail below in combination with examples.

[0027] Preparation example of low dielectric modified polyurethane resin Preparation example 1 The low dielectric modified polyurethane resin is prepared by the following method: Mix 40kg of polyester polyol, 3kg of 1,4-butanediol and 0.5kg of antioxidant 168, stir and mix at 70℃ and 200rpm for 1h, then add 30kg of polydimethylsiloxane, stir at 1000rpm for 30min at 100℃, stop stirring to get a gel-like substance, pour the gel-like substance into a mold for curing, break it to an average particle size of 3mm, and get the low dielectric modified polyurethane resin.

[0028] Preparation example 2 The low dielectric modified polyurethane resin is prepared by the following method: A mixture of 55 kg of polyester polyol, 6 kg of 1,4-butanediol and 1 kg of antioxidant 168 was mixed and stirred at 75°C at a rotation speed of 200 rpm for 1.5 h, then 40 kg of polydimethylsiloxane was added and stirred at 105°C at a rotation speed of 1250 rpm for 45 min, and then the stirring was stopped to obtain a gel-like substance, which was poured into a mold to be cured, broken into pieces with an average particle size of 3 mm, and a low-dielectric modified polyurethane resin was obtained.

[0029] Preparation Example 3 A low-dielectric modified polyurethane resin was prepared by the following method: A mixture of 70 kg of polyester polyol, 10 kg of 1,4-butanediol and 1.5 kg of antioxidant 168 was mixed and stirred at 80°C at a rotation speed of 200 rpm for 2 h, then 50 kg of polydimethylsiloxane was added and stirred at 110°C at a rotation speed of 1500 rpm for 60 min, and then the stirring was stopped to obtain a gel-like substance, which was poured into a mold to be cured, broken into pieces with an average particle size of 3 mm, and a low-dielectric modified polyurethane resin was obtained.

[0030] Preparation Example of composite wave-absorbing agent Preparation Example 4 A composite wave-absorbing agent was prepared by the following method: A. The raw materials Fe2O3, NiO, ZnO, La2O3 and CeO2 with the weights shown in Table 1 were mixed, deionized water was added, and ball milling was carried out at a rotation speed of 80 r / min for 6 h to obtain a slurry, PVA glue was added for continuous ball milling, followed by spray granulation, and then sintering at 1150°C for 1 h, and after cooling, La-Ce co-doped NiZn ferrite was obtained; B. 10 kg of La-Ce co-doped NiZn ferrite was dispersed in 20 kg of Ti3C2T X MXene dispersion liquid, Ti3C2T X The solid content of the MXene dispersion liquid was 10%, ultrasonic treatment was carried out for 40 min, stirring reaction was carried out at 65°C for 3 h, and ferrite@MXene core-shell particles were obtained; C. 10 kg of ferrite@MXene core-shell particles was dispersed in 2.5 kg of ZrO2 sol, the pH was adjusted to 8.0, and aging was carried out at 50°C for 2 h, and after centrifugation, drying was carried out at 120°C for 4 h, and a composite wave-absorbing agent was obtained.

[0031] Preparation Example 5 A composite wave-absorbing agent was prepared by the following method: A、mix the raw materials Fe2O3, NiO, ZnO, La2O3 and CeO2 in the weight shown in Table 1, add deionized water, ball mill at a speed of 80 r / min for 7 h to obtain a slurry, add PVA glue, continue to ball mill, then spray granulation, and then sinter at 1200℃ for 1.5 h, and obtain La-Ce co-doped NiZn ferrite after cooling; B、dispersing 10 kg of La-Ce co-doped NiZn ferrite in 30 kg of Ti3C2T X MXene dispersion liquid, Ti3C2T X The solid content of the MXene dispersion liquid is 12%; ultrasonic treatment for 60 min, stirring reaction at 75℃ for 4 h, to obtain ferrite@MXene core-shell particles; C、dispersing 10 kg of ferrite@MXene core-shell particles in 2.8 kg of ZrO2 sol, adjusting the pH to 8.5, aging at 55℃ for 2.5 h, drying at 135℃ for 5 h after centrifugation, to obtain a composite wave absorber.

[0032] Preparation Example 6 The composite wave absorber is prepared by the following method: A、mix the raw materials Fe2O3, NiO, ZnO, La2O3 and CeO2 in the weight shown in Table 1, add deionized water, ball mill at a speed of 80 r / min for 8 h to obtain a slurry, add PVA glue, continue to ball mill, then spray granulation, and then sinter at 1250℃ for 2 h, and obtain La-Ce co-doped NiZn ferrite after cooling; B、dispersing 10 kg of La-Ce co-doped NiZn ferrite in 40 kg of Ti3C2T X MXene dispersion liquid, Ti3C2T X The solid content of the MXene dispersion liquid is 15%; ultrasonic treatment for 80 min, stirring reaction at 85℃ for 5 h, to obtain ferrite@MXene core-shell particles; C、dispersing 9 kg of ferrite@MXene core-shell particles in 3 kg of ZrO2 sol, adjusting the pH to 9.0, aging at 60℃ for 3 h, drying at 150℃ for 6 h after centrifugation, to obtain a composite wave absorber.

[0033] Table 1 Raw material components and amounts (kg) in Preparation Examples 4-6

[0034] Preparation Example 7 The composite wave absorber differs from Preparation Example 4 in that no CeO2 is added in the raw materials of step A of the present preparation example, and the difference is replaced by Fe2O3.

[0035] Example Example 1 A low-defect wave-absorbing foam material, raw material components and proportions are shown in Table 2. Among them, the low-dielectric modified polyurethane resin is selected from the low-dielectric modified polyurethane resin prepared in Preparation Example 1; the composite wave-absorbing agent is selected from the composite wave-absorbing agent prepared in Preparation Example 4; the average particle size of the hollow glass microsphere is 5 mm; the organic silicon foam stabilizer is polyether modified polysiloxane; the antioxidant is antioxidant 1010; the crosslinking agent is trimethylolpropane; and the foaming agent is azodicarbonamide.

[0036] A low-defect wave-absorbing foam material is prepared by the following method: S1, the low-dielectric modified polyurethane resin is added to the mixer, heated to 50℃, and the composite wave-absorbing agent and fatty alcohol phosphate are added, stirred at 800 rpm for 15 min to obtain a pre-dispersion; S2, hollow glass microspheres, nano calcium carbonate, organic silicon foam stabilizer, antioxidant, crosslinking agent are added to the pre-dispersion of S1 in turn, heated to 65℃, stirred at 600 rpm for 25 min, and finally the foaming agent is added, stirred for 5 min to obtain the foaming slurry; S3, the foaming slurry is injected into the mold preheated to 40℃, pre-foamed at 45℃ for 15 min, and then heated to 65℃ for main foaming for 25 min; after foaming, it is heated to 85℃ for curing for 30 min, cooled to room temperature, and demolded to obtain the low-defect wave-absorbing foam material.

[0037] Example 2 A low-defect wave-absorbing foam material, raw material components and proportions are shown in Table 2. Among them, the low-dielectric modified polyurethane resin is selected from the low-dielectric modified polyurethane resin prepared in Preparation Example 2; the composite wave-absorbing agent is selected from the composite wave-absorbing agent prepared in Preparation Example 5; the average particle size of the hollow glass microsphere is 5 mm; the organic silicon foam stabilizer is polyether modified polysiloxane; the antioxidant is antioxidant 1010; the crosslinking agent is trimethylolpropane; and the foaming agent is azodicarbonamide.

[0038] A low-defect wave-absorbing foam material is prepared by the following method: S1, the low-dielectric modified polyurethane resin is added to the mixer, heated to 55℃, and the composite wave-absorbing agent and fatty alcohol phosphate are added, stirred at 900 rpm for 18 min to obtain a pre-dispersion; S2, hollow glass microspheres, nano calcium carbonate, organic silicon foam stabilizer, antioxidant, crosslinking agent are added to the pre-dispersion of S1 in turn, heated to 70℃, stirred at 700 rpm for 30 min, and finally the foaming agent is added, stirred for 6 min to obtain the foaming slurry; S3. Inject the foaming slurry into a mold preheated to 42°C, pre-foam at 48°C for 18 minutes, then raise the temperature to 68°C for 28 minutes for main foaming; after foaming, raise the temperature to 88°C for 35 minutes for curing, cool to room temperature and demold to obtain low-defect microwave absorbing foam material.

[0039] Example 3 A low-defect microwave absorbing foam material, the raw material composition and formulation of which are shown in Table 2. The low-dielectric modified polyurethane resin is selected from the low-dielectric modified polyurethane resin prepared in Preparation Example 3; the composite microwave absorbing agent is selected from the composite microwave absorbing agent prepared in Preparation Example 6; the average particle size of the hollow glass microspheres is 5 mm; the organosilicon foaming agent is polyether-modified polysiloxane; the antioxidant is antioxidant 1010; the crosslinking agent is trimethylolpropane; and the foaming agent is azodicarbonamide.

[0040] A low-defect microwave absorbing foam material is prepared by the following method: S1. Add low dielectric modified polyurethane resin to a mixer, heat to 60°C, add composite microwave absorbing agent and fatty alcohol phosphate, and stir at 1000 rpm for 20 minutes to obtain a pre-dispersion. S2. Hollow glass microspheres, nano calcium carbonate, organosilicon foaming agent, antioxidant, and crosslinking agent are added sequentially to the pre-dispersion liquid of S1. The temperature is raised to 75°C and stirred at 800 rpm for 35 minutes. Finally, the foaming agent is added and stirred for 8 minutes to obtain the foamed slurry. S3. Inject the foaming slurry into a mold preheated to 45°C, pre-foam at 50°C for 20 minutes, then raise the temperature to 70°C for main foaming for 30 minutes; after foaming, raise the temperature to 90°C for curing for 40 minutes, cool to room temperature and demold to obtain low-defect microwave absorbing foam material.

[0041] Table 2. Raw material composition and proportions (kg) of low-defect microwave absorbing foam materials in Examples 1-3

[0042] Example 4 A low-defect microwave absorbing foam material, which differs from Example 1 in that the organosilicon foam stabilizer used in this example is a fluorosilicone-modified polysiloxane.

[0043] Example 5 A low-defect microwave absorbing foam material, which differs from Example 1 in that the hollow glass microspheres in this example have a particle size of 2 mm.

[0044] Comparative Example Comparative Example 1 A low-defect microwave absorbing foam material, which differs from Example 1 in that an equal amount of unmodified polyurethane resin is used instead of its low-dielectric modified polyurethane resin in this comparative example.

[0045] Comparative Example 2 A low-defect wave-absorbing foam material, which is different from Example 1 in that an equal amount of conductive carbon black is used instead of the composite wave-absorbing agent in the present comparative example.

[0046] Comparative Example 3 A low-defect wave-absorbing foam material, which is different from Example 1 in that no hollow glass microspheres are added in the present comparative example, and the difference is made up by using low-dielectric modified polyurethane resin.

[0047] Comparative Example 4 A low-defect wave-absorbing foam material, which is different from Example 1 in that the composite wave-absorbing agent is selected from the composite wave-absorbing agent prepared in Preparation Example 7.

[0048] Performance detection test 1. For the wave-absorbing foam materials of Examples 1-5 and Comparative Examples 1-4, the mercury intrusion method is used to measure the volume of mercury intrusion into the pores of the wave-absorbing foam materials, and the proportion of the pore volume in the range of 3-5 mm pore size is counted. The higher the proportion, the better the pore size uniformity. The detection results are shown in Table 3.

[0049] 2. According to the method specified in GJB2038A-2011 Radar Wave-Absorbing Material Reflectivity Test Method, the wave-absorbing performance of the wave-absorbing foam materials of Examples 1-5 and Comparative Examples 1-4 is tested at high frequencies of 60 GHz and 70 GHz, respectively. The detection results are shown in Table 3.

[0050] Table 3 Detection Results

[0051] The 3-5 mm pore size proportion of Examples 1-5 is in the range of 93.7%-95.6%, which is at a very high level, indicating that the internal pore size of the material is highly concentrated, and there are no obvious large pores, cavities or broken pores and other defects. The reflectivity of Examples 1-5 at 60 GHz frequency band is -32.46 dB to -36.32 dB, and at 70 GHz frequency band is -31.76 dB to -34.69 dB, and the reflectivity values are all less than 30 dB, indicating that the wave-absorbing material has very high absorption efficiency for electromagnetic waves in the 45-70 GHz 5G millimeter wave core frequency band. It shows that the present application can effectively improve the absorption performance of the wave-absorbing material for high-frequency electromagnetic waves by adapting the composite wave-absorbing agent and the low-dielectric system.

[0052] The 3-5mm hole ratio of Comparative Example 1 is only 78.3%, and the 60GHz / 70GHz reflectivity is -19.67dB and -17.65dB, respectively, which is a significant performance decline compared to Example 1. Since the viscosity and flowability of the unmodified polyurethane resin cannot adapt to the foaming process, either the flowability is poor, causing the bubble growth to be blocked, or the flowability is too strong, causing the bubbles to escape during foaming, ultimately forming a large number of uneven-sized cells and cavities. The dielectric constant of the unmodified polyurethane resin is much higher than that of air, and the high-frequency electromagnetic wave is strongly reflected on the surface of the material, and cannot enter the interior to be absorbed by the composite wave-absorbing agent, resulting in a sharp drop in absorption efficiency.

[0053] The 3-5mm hole ratio of Comparative Example 2 is 93.6%, but the 60GHz / 70GHz reflectivity is only -10.67dB / -8.67dB, and the wave-absorbing performance is significantly attenuated. The core problem is that the conductive carbon black cannot adapt to the high-frequency band requirements, and most of the electromagnetic waves are reflected rather than absorbed, making it difficult to meet the requirements of the 5G millimeter wave scene.

[0054] The 3-5mm hole ratio of Comparative Example 3 is 82.3%, and the 60GHz / 70GHz reflectivity is -32.65dB / -30.17dB (close to Example 1), indicating that hollow glass microspheres have a certain promoting effect on maintaining the uniformity of the pore size of the wave-absorbing material.

[0055] The 3-5mm hole ratio of Comparative Example 4 is 92.1%, and the 60GHz / 70GHz reflectivity is -28.32dB / -27.62dB, and the wave-absorbing performance is lower than that of Example 1. The reason for the performance decline is the lack of Ce-doped regulation of the high-frequency magnetic properties of the ferrite core: La-Ce co-doping can synergistically regulate the magnetic crystal anisotropy constant of NiZn ferrite, suppressing the high-frequency magnetic moment relaxation hysteresis; after the absence of Ce, the magnetic permeability stability of the ferrite core in the 60-70GHz frequency band decreases, and the magnetic loss contribution weakens, resulting in a decrease in overall wave-absorbing efficiency.

[0056] This specific embodiment is merely an explanation of the present application, and is not a limitation on the present application. Those skilled in the art can make modifications to the present embodiment without creative contribution after reading the present specification, but as long as the scope of the claims of the present application is within the scope of the patent law.

Claims

1. A low-defect, wave-absorbing foam material, characterized by, The raw materials include the following weight components: Low dielectric modified polyurethane resin 45-65 parts; Composite wave absorber 10-18 parts; Hollow glass microbeads 2-6 parts; Organic silicon foam stabilizer 3-6 parts; Nano calcium carbonate 1-3 parts; Fatty alcohol phosphate 1-3 parts; Antioxidant 0.5-1.5 parts; Crosslinking agent 1-4 parts; Foaming agent 4-8 parts; The low dielectric modified polyurethane resin is a silicone modified polyurethane resin; The composite wave absorber takes La-Ce co-doped NiZn ferrite as a core, Ti3C2T X MXene / ZrO2 composite layer as a shell.

2. The low-defect wave-absorbing foam material of claim 1, wherein: The low dielectric modified polyurethane resin is prepared by the following method: The polyester polyol, the chain extender and the auxiliary agent are mixed and stirred at 70-80℃ for 1-2h, then the polydimethylsiloxane is added, and stirring is carried out at 100-110℃ and a speed of 1000-1500rpm for 30-60min, and then the stirring is stopped to obtain a gel-like substance, which is poured into a mold for curing, and then broken to obtain the low dielectric modified polyurethane resin.

3. The low-defect wave-absorbing foam material of claim 2, wherein, The raw material ratio of the low dielectric modified polyurethane resin is, in weight parts, polyester polyol 40-70 parts, chain extender 3-10 parts, polydimethylsiloxane 30-50 parts and auxiliary agent 0.5-1.5 parts.

4. The low-defect wave-absorbing foam material of claim 3, wherein, The chain extender is at least one of 1,4-butanediol and ethylene glycol; and the auxiliary agent is antioxidant 168.

5. The low-defect wave-absorbing foam material of claim 2, wherein: The composite wave absorber is prepared by the following method: A, the raw materials Fe2O3, NiO, ZnO, La2O3 and CeO2 are mixed, deionized water is added, and ball milling is carried out for 6-8h to obtain a slurry, PVA glue is added, and then ball milling is continued, followed by spray granulation, and then sintering at 1150-1250℃ for 1-2h, and then cooling to obtain La-Ce co-doped NiZn ferrite; B, La-Ce co-doped NiZn ferrite is dispersed in Ti3C2T X In the MXene dispersion liquid, the ferrite@MXene core-shell particles are obtained by ultrasonic treatment for 40-80 min, stirring reaction at 65-85 ℃ for 3-5 h. C, the ferrite@MXene core-shell particles are dispersed in ZrO2 sol, the pH is adjusted to 8.0-9.0, and then aging is carried out at 50-60℃ for 2-3h, and then centrifugation is carried out, and then drying is carried out at 120-150℃ for 4-6h to obtain the composite wave absorber.

6. The low-defect wave-absorbing foam material of claim 5, wherein: In step A, the mass ratio of Fe2O3, NiO, ZnO, La2O3 and CeO2 is (65-70):(10-13):(18-22):(1.2-2.0):(0.8-1.5).

7. The low-defect wave-absorbing foam material of claim 5, wherein: In step B, the La-Ce co-doped NiZn ferrite and Ti3C2T X The mass ratio of the MXene dispersion liquid is 1: (2-4); the Ti3C2T X The solid content of the MXene dispersion liquid is 10%-15%.

8. The low-defect wave-absorbing foam material of claim 5, wherein: In step C, the mass ratio of the ferrite@MXene core-shell particles to ZrO2 sol is (4-3):

1.

9. The low-defect wave-absorbing foam material of claim 1, wherein: The organic silicon foam stabilizer is any one of polyether modified polysiloxane and fluorosilicon modified polysiloxane.

10. A method of producing a low-defect wave-absorbing foam material according to any one of claims 1 to 9, characterized by, The method includes the following steps: S1, the low dielectric modified polyurethane resin is added into a mixer, and the temperature is raised to 50-60℃, then the composite wave absorber and the fatty alcohol phosphate are added, and stirring is carried out at a speed of 800-1000rpm for 15-20min to obtain a pre-dispersion liquid; S2, the hollow glass microbeads, the nano calcium carbonate, the organic silicon foam stabilizer, the antioxidant, the crosslinking agent are added into the pre-dispersion liquid of S1 in sequence, the temperature is raised to 65-75℃, and then stirring is carried out at a speed of 600-800rpm for 25-35min, and finally the foaming agent is added and stirred for 5-8min to obtain a foaming slurry; S3, the foaming slurry is injected into a mold preheated to 40-45℃, pre-foamed at 45-50℃ for 15-20min, then heated to 65-70℃ for main foaming for 25-30min; after foaming is completed, heated to 85-90℃ for curing for 30-40min, cooled to room temperature, then demolded to obtain a low-defect wave-absorbing foam material.

Citation Information

Patent Citations

  • A foam carbon wave-absorbing material, its preparation method and application

    CN114883813B

  • Wave-absorbing foam and preparation method thereof

    CN114853422A

  • Wave-absorbing thermoplastic elastomer foam material and preparation method thereof

    CN115260735A

  • Wave-absorbing polyurethane composite foam and preparation method thereof

    CN115975372A